Patterns of Poisoning Cases Reported in the Baghdad Poisoning Control Center during 2014 - Hasan Alhaddad Alhaddad (College of Pharmacy / Mustansiriyah University, 2018)
Poisoning is an important clinical emergency and represents a major contributor to morbidity and mortality worldwide. However, early diagnosis and management of poisoning significantly affect mortality and morbidity as well as health care costs. Understanding the characteristic of poisoning cases is important for treatment. The present study investigated the characteristic of poisoning cases in Baghdad Poisoning Control Center (PCC). Data on all poisoning cases reported in Baghdad PCC during 2014 were retrospectively obtained from the medical records. A total of 804 reports of poisoning caseswere analyzed according to geographical distribution, age of victims, gender, the type and class of poisoning agent, and the follow up after poisoning. The results of this study showed thenecessity to continue collecting data of patients admitted to emergency departments and poisoning control centers andaddress the main obstacles facing the management of poisoning cases and decrease morbidity and mortality.